2020
DOI: 10.1094/pdis-04-19-0753-re
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Molecular Mapping of a Gummy Stem Blight Resistance Gene in Wild Watermelon (Citrullus amarus) Germplasm PI 189225

Abstract: Gummy stem blight (GSB), caused by Stagonosporopsis cucurbitacearum (syn. Didymella bryoniae), is a destructive foliar disease of watermelon in areas with hot and humid climates. The wild watermelon germplasm PI 189225 is a known source of resistance to GSB. The identification and use of molecular markers linked to resistance genes in the wild-type germplasm will speed up the introgression of GSB resistance into new watermelon varieties. An F2 segregating population was obtained from a cross between the resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 56 publications
3
42
0
Order By: Relevance
“…Gusmini et al (2005) reported a low correlation (r = 0.10 -0.36) in the evaluation for GSB resistance in watermelon. More recently, Ren et al (2019) reported a significantly high correlation (r = 0.92) for GSB disease incidence in watermelon seedlings between two greenhouse experiments. We calculated a relatively high (72.6%) broad sense heritability, with no significant interaction observed between the genotype × experiment.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Gusmini et al (2005) reported a low correlation (r = 0.10 -0.36) in the evaluation for GSB resistance in watermelon. More recently, Ren et al (2019) reported a significantly high correlation (r = 0.92) for GSB disease incidence in watermelon seedlings between two greenhouse experiments. We calculated a relatively high (72.6%) broad sense heritability, with no significant interaction observed between the genotype × experiment.…”
Section: Discussionmentioning
confidence: 95%
“…The total number of genes in the 2-LOD confidence interval for each QTL were: ClGSB3.1: 65; ClGSB5.1: 712; ClGSB7.1: 574 (Electronic Supplementary Material 4). The GSB resistance loci and candidate genes identified in the present study were compared with those identified previously in cucurbit species (Lou et al 2013;Liu et al 2017;Zhang et al 2017;Hassan et al 2018;Hu et al 2018;Ren et al 2019).…”
Section: Candidate Gene Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The original files generated from high-throughput sequencing were converted to raw reads by using base calling software Illunima Casava 1.8, the quality evaluation was performed to obtain clean reads as described by Ren et al (2019) [51]. Then, the filtered short reads were aligned to the reference Chinese cabbage genome (http://brassicadb.org/brad/) using the BWA (Burrows-Wheeler-Aligner) software [52].…”
Section: Alignment With the Reference Genome And Variant Callingmentioning
confidence: 99%